Chip‐Scale Fabrication of Uniform Lead Halide Perovskites Microlaser Array and Photodetector Array. Issue 1 (13th December 2017) - Duan, Zonghui; Wang, Yujie; Li, Gang; Wang, Shuai; Yi, Ningbo; Liu, Shuai; Xiao, Shumin; Song, Qinghai
Abstract: Lead halide perovskites have recently attracted attention due to their outstanding photoelectric properties. Hence, perovskite‐based optoelectronic devices are widely studied. Herein, a simple solution‐based one‐step anti‐solvent method to produce well‐controlled and uniform CH3 NH3 PbBr3 ‐based micro‐devices is reported. It is confirmed that the size and mode numbers of the self‐assembled microdisk cavities can be well controlled by modifying the size of the SiO2 microdisks on the substrate or changing the concentration of the perovskite precursor. With this simple and robust method, the produced CH3 NH3 PbBr3 microdisk arrays are extremely uniform in both their size distribution and emission spectra. Moreover, a perovskite photodetector array with fast rise (<8.3 ms) and decay (<8.3 ms) times was fabricated by periodically patterning the substrate. Based on the high controllability and high reproducibility of the patterned CH3 NH3 PbBr3 microdisk arrays, this cost‐effective and mass‐manufacturable approach significantly increases the production yield of lead halide perovskite microdevices and boosts their ability to be used in practical applications. Abstract : A uniform CH3 NH3 PbBr3 micro‐device array is fabricated with a facile solution‐based syntheses. Each CH3 NH3 PbBr3 microdisk on the same wafer shows identical size and shape. Moreover, these CH3 NH3 PbBr3 cavities exhibit homogenous laser spectra with negligibly small standard deviation in wavelength. By controlling the sizes of SiO2 microdisks or the concentration of MAPbBr3 precursor solution, the CH3 NH3 PbBr3 cavity size can be precisely modified.